Natural Deep Eutectic Solvent-Based Extraction of Malva sylvestris L.: Phytochemical Content, Antioxidant and Antimicrobial Potential - Neli Memdueva; Milena Tzanova; Zvezdelina Yaneva; Nikolina Rusenova; Neli Grozeva; Toncho Dinev (Separations, 2025)
Malva sylvestris L. is a herbaceous plant, distributed worldwide, rich in biological active compounds, and known for its health benefits. In this study, extracts from different parts (leaves, flowers, and roots) of this plant were prepared using green classic (70% ethanol) and natural deep eutectic solvents (NADESs) based on choline chloride and acetic acid (NADES1) or glycerol (NADES2). Their antioxidant, antibacterial (against B. cereus, S, aureus, E. coli, and P. aeruginosa), and antifungal activity (against P. chrysogenum, F. oxysporum, A. parasiticus, A. flavus, A. niger A. carbonarius, and A. ochraceus) were compared. Ethanolic extracts were characterized with the highest total contents of phenols, flavonoids, and condensed tannins. Ethanolic and NADES flower extracts were the richest in the antioxidants tested. Alkaloids were extracted in low quantities. The experimentally determined antioxidant potential of the extracts proved the highest DPPH scavenging activity of ethanolic extracts and the lowest of NADES1 extracts. The ABTS scavenging capacity of NADES1 and ethanolic extracts displayed comparable results, while NADES2 extracts were characterized as having the highest FRAP activity. NADES1 extracts manifested pronounced antibacterial activity, partially due to the low pH of the pure solvent, as well as inconsistent antifungal activity—from moderate to a complete lack of activity. A strong positive correlation was reported between the DPPH radical scavenging capacity and phenolic compound content. Future detailed investigations on the mechanism of the antimicrobial activity of NADES1 extracts are necessary to clarify the observed phenomenon of the decreased antifungal potential of NADES1 extracts compared to the pure solvent NADES1.